Spontaneous uterine vessel perforation in late pregnancy following in vitro fertilisation: a rare cause of near miss maternal morbidity and fetal death - Gainder, Shalini; Muthyala, Tanuja; Chandra Saha, Subhas (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Spontaneous perforation of uterine vessels causing hemoperitoneum in pregnancy is rare and is associated with high perinatal and maternal mortality and morbidity. However, for the clinician identification of aetiology with ongoing resuscitation is important in order to affect the proper treatment. Case report: We report a case of spontaneous hemoperitoneum in pregnancy following IVF conception due to ruptured uterine vein successfully managed with emergency laparotomy and repair of the uterine vessel. Conclusion: Clinicians should be aware of such rare and potentially fatal complications after IVF, because early diagnosis and management in these cases can yield a favourable maternal and perinatal outcome.